Hubungan Kepatuhan Pembatasan Cairan dan Konsumsi Sodium terhadap Overload Cairan Pasien Ginjal Kronik yang Menjalani Hemodialisa - Thalita Apriliani; Retno Setyawati; Erna Melastuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Chronic kidney disease patients undergoing hemodialysis are vulnerable to fluid overload due to impaired renal excretion and dietary nonadherence. This cross sectional correlational study examined the relationship between fluid restriction adherence and sodium intake with fluid overload among one hundred chronic kidney disease patients receiving maintenance hemodialysis at Sultan Agung Islamic Hospital Semarang during September to October 2025. Data were collected using a modified End Stage Renal Disease Adherence Questionnaire, a semi quantitative food frequency questionnaire, and interdialytic weight gain measurements. Chi Square analysis demonstrated a significant association between fluid restriction adherence and fluid overload, as well as between sodium intake and fluid overload, with p values below 0.05. Patients who adhered to fluid restriction and reported infrequent sodium intake predominantly experienced mild fluid overload, whereas nonadherent patients and those with frequent sodium intake showed higher proportions of severe overload. These findings indicate that behavioral dietary factors play a critical role in determining hydration status among hemodialysis patients. Strengthening patient education, family involvement, and nursing based dietary management remains essential.